ECOLOGICAL AND MANAGEMENT ASPECTS OF Cyrtomenus bergi Froeschner, SMALLPOX BUG IN THE YUCCA CULTIVATION (Maniot esculenta Crantz) - ARIAS-V., BERNARDO; BELLOTTI, ANTHONY C. (Revista Colombiana de Entomología, 1985)
The subterranean chinch bug, Cyrtomenus bergi Froeschner (Hemiptera: Cydnidae) is an insect that attacks the roots of cassava, reducing its commercial value by more than 500/o. The complete life cycle of the insect is over 500 days thereby remaining in the soil throughout the vegetative period of the crop. Due to the importance of this pest a research program was designed to obtain the basic information needed to recommend adequate control measures. These studies íncluded: 1) Determination of the time required for initial damage symptoms to appear; 2) determination of the population fluctuation in the field and the appearance of damage symptoms; 3) studies on varietal preference betwenn roots of sweet and bitter varieties (high and low HCN content); 4) chemical control. Results show that the initial damage symptoms, under laboratory conditions, begin to appear within 24 hours alter feeding is initiated. Under field conditions, the initiation of roots attack by C. bergi occurs during the first month of plant growth and there is a preference for feeding on sweet over bitter roots. The use of pesticides, such as dimethoate can reduce pest intended.